INFLUENCE OF ANIMATION MEDIA USE AND LEARNING STYLE ON THE RESULTS OF LEARNING THE CONCEPT OF MOTION IN PLANTS STATE JUNIOR HIGH SCHOOL STUDENTS 11 BANDA ACEH - Cut Shaila Utami; Qurratu Aini; Azhar Amsal (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
Biology learning in class VIII2 SMP Negeri 11 Banda Aceh shows unsatisfactory results from academic achievement, especially the concept of motion in plants. This is indicated by the average value of student learning completeness which is still below the KKM, which is 70 and thus required to take remedial (repeat). This study aims to determine the effect of animation media and learning styles on learning outcomes in class VIII2 students of SMP Negeri 11 Banda Aceh on the concept of motion in plants. The approach used in this research is a quantitative approach with the type of experimental research. The population is class VIII2 students, totaling 33 students. Collecting data using a questionnaire and post-test. The research data were analyzed using the t-test formula. The results of the study obtained the value of tcount ttable or 6.99 1.69. In accordance with the test criteria, the hypothesis Ha is accepted and Ho is rejected, thus it can be concluded that there is a significant influence between animation media and learning styles on student learning outcomes in class VIII2 SMP Negeri 11 Banda Aceh the concept of motion in plants.Keywords: Animation Media, Learning Style, Movement in Plants, Learning Outcomes.